Ang-(1-7) is an endogenous β-arrestin-biased agonist of the AT1 receptor with protective action in cardiac hypertrophy - Larissa B. Teixeira (Nature Portfolio, 2017)
Abstract The renin-angiotensin system (RAS) plays a key role in the control of vasoconstriction as well as sodium and fluid retention mediated mainly by angiotensin (Ang) II acting at the AT1 receptor (AT1R). Ang-(1-7) is another RAS peptide, identified as the endogenous ligand of the Mas receptor and known to counterbalance many of the deleterious effects of AngII. AT1R signaling triggered by β-arrestin-biased agonists has been associated to cardioprotection. Because position 8 in AngII is important for G protein activation, we hypothesized that Ang-(1-7) could be an endogenous β-arrestin-biased agonist of the AT1R. Here we show that Ang-(1-7) binds to the AT1R without activating Gq, but triggering β-arrestins 1 and 2 recruitment and activation. Using an in vivo model of cardiac hypertrophy, we show that Ang-(1-7) significantly attenuates heart hypertrophy by reducing both heart weight and ventricular wall thickness and the increased end-diastolic pressure. Whereas neither the single blockade of AT1 or Mas receptors with their respective antagonists prevented the cardioprotective action of Ang1-7, combination of the two antagonists partially impaired the effect of Ang-(1-7). Taken together, these data indicate that Ang-(1-7) mediates at least part of its cardioprotective effects by acting as an endogenous β-arrestin-biased agonist at the AT1R.